The Characcteristics and Application of Syntactic Analogy - Mohammad Ebrāhīm Khalīfe Shushtari (دراسات في اللغة العربيّة وآدابها)
This article examines the role analogy plays in syntactic and morphology. It does not examine the definitions or the types of syntactic analogy, nor its basic elements because it addresses scholars with solid knowledge about syntactic analogy and its advantages. This type of analogy has many characteristics, which distinguish it from other types. Certainly, it has pervaded all domains of syntax and morphology and has established its undeniable importance. Accounting for this type of analogy can enhance the scientific level of the field of syntactic studies .